POWER BANK PORTABLE SOLAR CHARGER MENGGUNAKAN SISTEM BUCK-BOOST CONVERTER BERBASIS MIKROKONTROLER ATMEGA 32 - Elfani, Nisrina Zahra; Sasmoko, Priyo (Gema Teknologi, 2016)
Nisrina Zahra Elfani, Priyo Sasmoko explain that portable electronic devices have a problem, namely the resistance of electrical energy intake, because these electronic devices get energy from batteries that have limited capacity to store electrical energy. Electronic objects that have now mushroomed and become primary needs such as cellphones and laptops desperately need a tool to recharge batteries. Solar energy can be used to recharge the gatget batteries by converting them to electric power. This will be very useful for those who are field workers, travelers, and nature lovers who need battery charging devices without having to use an adapter that uses an AC source from PLN grids in homes, while in certain circumstances gadget users may not be at home or in a place that provides ac resources. One solution to this problem is the use of a power bank portbale solar charger. Portable power bank solar charger is a charger that is equipped with backup batteries and solar cells as a source of electrical energy. Realized a portable charger that uses the working principles of DC-DC converter circuits such as: buck-boost converter, buck converetr and boost converter as a voltage regulator that is used to charge electronic devices. The ADC channel on the microcontroller is used as feedback for the controller that is also present in the microcontroller used so that the converter output can be maintained at a certain value through setting the duty cyle PWM that drives the converter. This portable power bank solar charger uses a buck-boost converter system and can produce the desired voltage. Buck converters can reduce the output voltage from 5 Volt dc for the use of chargering handphone and boost converter can increase the output voltage around 19 volts dc for the use of notebook charging Keywords: powerbank, portable charger, buck-boost converter, solar cellReferencesGunawan. 2009. Rancang Bangun DC-Dc Converter dengan PID Diskrit sebagai Pengendali Tegangan Keluaran. Skripsi. Depok :  Fakultas Teknik, Program Studi Elektro, Universitas  Indonesia. Handini, Wulandari. 2008. Performa Sel Surya Tersensitasi Zat Pewarna (DSSC) Berbasis ZnO dengan Variasi Pengisian dan Besar Kristalis Ti . Skripsi. Depok : Fakultas Teknik, Program Studi Elektro, Universitas  Indonesia.Hidayat, Suryo, Muhamad. 2010. Rancang Bangun buck Boost Konverter.  Skripsi. Depok : Fakultas Teknik, Program Studi Elektro, Universitas  Indonesia